The Study of High Voltage AC Generation Using A Series Resonant Circuit - Peerawut Yutthagowith; Jedsada Raxsa; Punyavee Chaisiri; Thanatorn Mai-eiam (My University, 2023)
This paper studies an approach for high-voltage AC generation using a series resonant circuit in case of high capacitive load. The capacitor of 0.5 microfarad was a selected capacitive load in the test circuit. An HV inductor with 3 changing taps (53.2 H, 24.2 H, and 18.6 H) is used in the circuit for the generation of AC voltage with frequencies of about 30 Hz, 40 Hz, and 50 Hz, respectively. The square wave was generated by a variable frequency converter. The frequency of the square wave is adjusted to meet the resonant conditions associated with the inductance and capacitance of the circuit. It was found that using the test circuit the voltage gains of 30 can be achieved in the experiments. From the test results, it can confirm the possibility for further development of the test circuit used in the onsite test of MV and HV power cables in the near future.
Keywords: Advanced DC-DC Converters; Multilevel Inverters and Converters; Engineering Applied Research